Pengaruh Kualitas Produk, Gaya Hidup dan Kepribadian terhadap Keputusan Pembelian Sepeda Motor PCX di Kecamatan Blora Kabupaten Blora - Oktaviani, Shinta; Nina Adelina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this study was to determine the effect of product quality, lifestyle and personality on purchasing decisions for Honda PCX motorcycles in Blora Blora subdistrict, either partially or simultaneously. The research method used by the population is consumers who come to Honda motorbikes in Blora Blora Regency. The sample of this research is 96 respondents. Data collection techniques using a questionnaire. The analytical tools used are instrument tests (validity test, reliability test), classical assumptions (normality test, multicollinearity and heteroscedasticity test), hypothesis test (multiple linear regression analysis, t test, F test and coefficient of determination test (R2). The results showed that the variables of product quality, lifestyle and personality had a significant influence on purchasing decisions for Honda PCX motorbikes in Blora Blora District partially or simultaneously.